2021
DOI: 10.1142/s0218957721500135
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy on Pressure-Biofeedback Guided Craniocervical Flexion Exercise in Neck Pain: A Randomized Controlled Trial

Abstract: Objective: Neck pain is a common cause of disability and costly problem, especially in the working population. However, there is a paucity of studies examining the efficacy of pressure-biofeedback guided craniocervical flexion exercise (CCFE) in neck pain. Therefore, this study aims to find out the efficacy of Pressure-Biofeedback guided CCFE on the treatment of neck pain. Methods: This randomized controlled trial included 60 participants with neck pain who were randomly assigned to the experimental group ([Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, these interventions typically do not have high-quality, long-term studies demonstrating successful improvements in HRQoL or patient-reported outcomes. Physical medicine and rehabilitation investigations have reported some positive pain outcomes but do not often report improvements in coronal and sagittal postural and spine balance parameters with the long-term stability of the successful intervention [30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…However, these interventions typically do not have high-quality, long-term studies demonstrating successful improvements in HRQoL or patient-reported outcomes. Physical medicine and rehabilitation investigations have reported some positive pain outcomes but do not often report improvements in coronal and sagittal postural and spine balance parameters with the long-term stability of the successful intervention [30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Karthi et al [ 16 ] concluded that endurance exercises with pressure feedback for deep cervical flexor muscles in mechanical neck pain was significantly effective in reducing pain compared to deep cervical flexor exercises with visual biofeedback. Lwin et al [ 17 ] conducted a study of 60 people having neck pain randomly divided into 2 groups, experimental and control. While the experimental group received pressure-biofeedback guided cranio-cervical flexion exercise four times per week for four weeks, the control group received electrotherapy agents (TENS and radiant heat).…”
Section: Discussionmentioning
confidence: 99%
“…There was a more significant reduction in the NDI scores in the experimental group than the control group at week 4. The pressure-biofeedback guided cranio-cervical flexion exercise found useful for improving pain and functional disability on neck pain [ 17 ]. In the present study, the group in which the exercises were performed with a stabilizer was found to have better results than the conventional group.…”
Section: Discussionmentioning
confidence: 99%